Corporate entrepreneurship and financial performance: The role of management - C. J. Goosen; T. J. De Coning; E. V.D.M. Smit (South African Journal of Business Management, 2002)
It is hypothesised that a positive relationship exists between the financial performance of an organisation and the level of intrapreneurship within the organisation with causation running from entrepreneurship to financial outcomes. Using a three-factor key intrapreneurship model developed by Goosen, De Coning and Smit (2002) and financial outcomes from a sample of companies listed in the industrial sector of the Johannesburg Stock Exchange, this proposition is put to the test. The results support the hypothesis that the key factors innovativeness, proactiveness and management's internal influence all significantly contribute to financial performance if regarded individually, but that the last factor dominates the first two external factors when used simultaneously. The conclusion underscores the importance of the impact of leadership on financial outcomes.
Keywords: 650